Heme oxygenase-1 attenuates cadmium-induced mitochondrial-caspase 3- dependent apoptosis in human hepatoma cell line. Issue 1 (December 2015) - Lawal, Akeem; Marnewick, Jeanine; Ellis, Elizabeth
Abstract Background Cadmium (Cd) is a well known environmental and industrial toxicant causing damaging effects in numerous organs. In this study, we examined the role of heme oxygenase-1 (HO-1) in modulating the Cd-induced apoptosis in human hepatoma (HepG2) cells after 24 h exposure. Methods HepG2 cells were exposed to 5 and 10 μM Cd as CdCl2 for 24 h while other sets of cells were pre-treated with either 10 μM Cobalt protoporphyrin (CoPPIX) or 10 μM Tin protoporphyrin (SnPPIX) for 24 h, or 50 μM Z-DEVD-FMK for 1 h before exposure to 5 and 10 μM CdCl2 for 24 h. Expressions of caspase 3, cytosolic cytochrome c, mitochondrial Bax and anti-apoptotic BCL-xl proteins were assessed by western blot. Intracellular reactive oxygen species (ROS) production was determined using the dihydrofluorescein diacetate (H2 DFA) method. Cell viability was assessed by MTT assay, while a flow cytometry method was used to assess the level of apoptosis in the cell populations. Results Our results show that there were a significant increase in the expression of cytosolic cytochrome c, mitochondrial Bax protein, and caspase 3 at 5 and 10 μM compared to the control, but these increases were attenuated by the presence of CoPPIX. The presence of SnPPIX significantly enhanced Cd-induced caspase 3 activities. CoPPIX significantly decreased the level of ROS production by 24.6 and 22.2 % in 5 and 10 μM CdCl2, respectively, but SnPPIX caused a significant increase in ROS production in the presence of CdCl2 . HepG2 cell viability was also significantly impaired by 13.89 and 32.53 % in the presence of 5 and 10 μM CdCl2, respectively, but the presence of CoPPIX and Z-DEVD-FMK significantly enhanced cell survival, while SnPPIX enhanced Cd-impaired cell viability. The presence of CoPPIX and Z-DEVD-FMK also significantly decreased the population of apoptotic and necrotic cells compared with Cd. Conclusion In summary, the present study showed that HO-1 attenuates the Cd-induced caspase 3 dependent pathway of apoptosis in HepG2 cells, probably by modulating Cd-induced oxidative stress.